Preserving the Mandailing Language through a Mobile Mandailing–Indonesian Dictionary - Muhammad Hasyimsyah Batubara; Fitri Ayu (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2025)
The fact that younger people do not speak it and that Indonesian and other languages are more common makes it harder for the Mandailing language to survive as a cultural legacy. According to what we saw, the younger generation does not know 40 to 50 percent of Mandailing words, including siriaon (joy) and ancim (salty). This project aims to create a digital dictionary application that will preserve the Mandailing language using technology. This project uses a descriptive qualitative approach and the Research and Development process to investigate how the younger generation views the demand for apps and create a digital dictionary prototype in Mandailing-Indonesian. The application’s limited testing revealed that users enjoyed it. According to the study’s findings, if mobile apps incorporate cultural content, community engagement, and flexible design, they could be an effective tool for preserving languages. This study contributes to efforts to revitalize regional languages through technology for youth effectively.